UNCITRAL – Traditions and Perspectives - Marinova, Diana (UNWE Yearbook, 2018)
The subject of this paper is to identify the role and importance of the UN Commission on International Trade Law (UNCITRAL) – one of most popular UN organizations. Its main functions and objectives have been analyzed, especially with regard to the law-making process. The main goal of this piece of research is to outline the perspectives of UNCITRAL pertaining to the improvement of its functions and texts and, mostly of the model laws. The coordination between organizations assisting the UNCITRAL’s activities in the attempt to harmonize and modernize its legal instruments has been given priority in this paper.The UNCITRAL rules are applicable also in Bulgaria and this is one of most important reasons of this study.